Identifying and interpreting spatiotemporal variation in diagnoses of infectious syphilis among men, England: 2009 to 2013. (4th May 2016) - Petersen, Jakob; Gibin, Maurizio; Sile, Bersabeh; Simms, Ian
Abstract : Objectives: Spatial clusters and variations in the trajectory of local epidemics were explored in relation to sexual orientation, demographic factors, stage of syphilis infection and HIV serostatus. Methods: Kulldorff's scan statistics (SaTScan) was used to distinguish endemic and temporary clusters using a two-stage analysis. Results: Endemic areas were found in London, Manchester, Brighton and Blackpool. Up to 40% of diagnoses were found within an 11 km radius of central London. Of men diagnosed with syphilis in London, 80% were men who have sex with men (MSM). Annual incidence in London increased from 24 cases (95% CI 23 to 26) per 100 000 male population in 2009 to 36 cases (95% CI 34 to38) in 2013. In comparison with clusters, endemic areas were characterised by a significantly higher (p<0.05) proportion of MSM (83% compared with 73%), increased HIV positivity (41% vs 15%), age 35 to 44 years (34% vs 23%), a lower proportion of patients born in the UK (50% vs 79%) and a lower proportion of primary stage infection (40% vs 47%). Space–time clusters outside endemic areas occurred in urban and rural areas and diagnoses fluctuated below 10 per month. Exponential increases in diagnoses resembling point source outbreaks were seen at two locations. Conclusion: Control of syphilis in endemic areas has proved elusive and clusters present unique intervention opportunities. Investigating the diversity of local epidemics provides information that can be used to predict outbreak structure, plan and evaluate sexual health services and guide public health investigation, hypothesis generation and research.